THE SUFFERING OF THE ALGERIAN PEOPLE UNDER FRENCH COLONIALISM WRITTEN BY "MOHAMED DEEB""A HISTORICAL READING THROUGH THE NOVEL "THE BIG HOUSE" - Asma Jadallah Khasawneh; Khader Eid Al Sarhan (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
The Arab Maghreb countries in general, and Algeria in particular, suffered from the scourge of colonialism, as the French colonizer dared in an attempt to change the features of Algeria and the people in various respects, and tried to obliterate the national identity by various means. Before this attack, the sons of Algeria rushed to defend their homeland. Some of them carried arms and others used their pens in writing to show the world the injustice and oppression of the colonizer. Between our hands, a trilogy novel that records the state of the Algerian people during the colonial stage. It was written in French and translated into Arabic by the Algerian writer Mohamed Deeb. This trilogy is consisting of three novels. The researchers addressed the first novel "that is called the Big House, and reviewed the situation of the Algerian people under the French colonial in general. It gives us plenty of information about the conditions of the Algerian people under French colonialism. In that period, the characters and the places where the events take place are vivid examples of the Algerian people where we can touch the following situation: a) economic situation throughout talking about hunger and poverty, b) the social conditions that talked about the relations between the residents of Sbeitar's House and the composition of the Algerian society. c) the educational situation by talking about the school, and d) the political issues that deal with freedom and the colonial tracking down for the resistance. In addition, we can touch the reality and suffering of the childhood and woman, so the child and his mother constitute the core focus in this novel, they act as a general case of the Algerian people under French colonialism.